2002
DOI: 10.1182/blood-2002-04-1150
|View full text |Cite
|
Sign up to set email alerts
|

Unrelated stem cell transplantation in multiple myeloma after a reduced-intensity conditioning with pretransplantation antithymocyte globulin is highly effective with low transplantation-related mortality

Abstract: We investigated the feasibility of unrelated stem cell transplantation in 21 patients with advanced stage II/III multiple myeloma after a reduced-intensity conditioning regimen consisting of fludarabine (150 mg/m 2 ), melphalan (100-140 mg/m 2 ), and antithymocyte globulin (ATG; 10 mg/kg on 3 days). The median patient age was 50 years (range, 32-61 years). All patients had received at least one prior autologous transplantation, in 9 cases as part of an autologous-allogeneic tandem protocol. No graft failure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
110
0
4

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(123 citation statements)
references
References 32 publications
9
110
0
4
Order By: Relevance
“…The median OS was 15 months and it was better in patients who received the RICT as planned consolidation of a single autograft. The two-step approach was also employed with success by Kro¨ger et al [21] in 42 patients with unrelated/mismatched donors. Carella et al [22] confirmed the feasibility of the sequential combination of APBSCT and RICT.…”
Section: Discussionmentioning
confidence: 99%
“…The median OS was 15 months and it was better in patients who received the RICT as planned consolidation of a single autograft. The two-step approach was also employed with success by Kro¨ger et al [21] in 42 patients with unrelated/mismatched donors. Carella et al [22] confirmed the feasibility of the sequential combination of APBSCT and RICT.…”
Section: Discussionmentioning
confidence: 99%
“…23,24,[40][41][42][43][44] This is not surprising, because irrespective of the treatment modality analyzed, relapsed and refractory patients will inherently have a shorter PFS and OS than patients in first remission. However, in contrast to earlier studies, new agents were available to most of our patients who relapsed after allogeneic transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Encouraging results have been reported, with a TRM of B20-21% at 2 and 3 years. 34,35 Clearly, further prospective trials are warranted to define better the role of RIC MUD Allo SCT for patients with myeloma.…”
Section: Allosct In Multiple Myeloma-the Historymentioning
confidence: 99%
“…33 The role of RIC MUD AlloSCT remains to be defined although recent results have reported a TRM of B20%. 33,34 Clearly, further prospective trials are warranted to better define the role of RIC MUD Allo SCT for patients in the first treatment phase for myeloma. Similarly, the use of umbilical cord stem cells as a source for GvM has been reported in a limited number of case reports, but only in patients with advanced disease, 39,40 and again should be explored only as part of a clinical study protocol.…”
Section: Allosct In Multiple Myeloma-clinical Decision Makingmentioning
confidence: 99%